CYP450 polymorphisms and clinical pharmacogenetics of ibuprofen after lower third molar extraction - Giovana M. Weckwerth; Thiago J. Dionísio; Yuri M. Costa; Bella L. Colombini-Ishiquiriama; Gabriela M. Oliveira; Elza A. Torres; Leonardo R. Bonjardim; Adriana M. Calvo; Troy Moore; Devin M. Absher; Carlos F. Santos (European Journal of Clinical Pharmacology, 2021)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Phylogeography and adaptation genetics of stickleback from the H aida G waii archipelago revealed using genome‐wide single nucleotide polymorphism genotyping - Bruce E. Deagle; Felicity C. Jones; Devin M. Absher; David M. Kingsley; Thomas E. Reimchen (Molecular Ecology, 2013)
Threespine stickleback populations are model systems for studying adaptive evolution and the underlying genetics. In lakes on the H aida G waii archipelago (off western C anada), stickleback have undergone a remarkable local radiation and show phenotypic diversity matching that seen throughout the species distribution. To provide a historical context for this radiation, we surveyed genetic variation at >1000 single nucleotide polymorphism ( SNP ) loci in stickleback from over 100 populations. SNP s included markers evenly distributed throughout genome and candidate SNP s tagging adaptive genomic regions. Based on evenly distributed SNP s, the phylogeographic pattern differs substantially from the disjunct pattern previously observed between two highly divergent mt DNA lineages. The SNP tree instead shows extensive within watershed population clustering and different watersheds separated by short branches deep in the tree. These data are consistent with separate colonizations of most watersheds, despite underlying genetic connections between some independent drainages. This supports previous suppositions that morphological diversity observed between watersheds has been shaped independently, with populations exhibiting complete loss of lateral plates and giant size each occurring in several distinct clades. Throughout the archipelago, we see repeated selection of SNP s tagging candidate freshwater adaptive variants at several genomic regions differentiated between marine–freshwater populations on a global scale (e.g. EDA , Na/K ATP ase ). In estuarine sites, both marine and freshwater allelic variants were commonly detected. We also found typically marine alleles present in a few freshwater lakes, especially those with completely plated morphology. These results provide a general model for postglacial colonization of freshwater habitat by sticklebacks and illustrate the tremendous potential of genome‐wide SNP data sets hold for resolving patterns and processes underlying recent adaptive divergences.